Inventory and Registry Development of Ornamental Tree Saplings in Urban Areas to Assess their Survival Rate - Alikulovich, Sobirov Ulmas (American Journal of Biology and Natural Sciences, 2025)
Although the inventory and registry development of ornamental tree saplings planted in urban areas is one of the most pressing issues today, to date, no scientific or regulatory-legal documents have been developed in Uzbekistan to define the procedures for inventorying saplings planted across various ecosystems of the country. Recognizing this gap, we have developed a procedure for conducting an inventory of ornamental tree saplings and establishing their registry. In this procedure, data on ornamental trees and shrubs are compiled in tabular form, and their enumeration is carried out using a method not previously applied in practice. Specifically, a counting technique that is not commonly used in the field of dendrology has been implemented for sapling inventory. Currently, this enumeration method is not utilized in standard practice. This article defines and proposes a procedure for the inventory and registry of ornamental tree saplings that aligns with contemporary needs and practical requirements.